Modeling Rainfall-Runoff Relations Using HEC-HMS in an Oil Palm Catchment for Double Rain Events in Labu River Basin of Peninsular Malaysia - Adesiji, A. R.; Odekunle, M. O.; Mangey, J. A.; Adeyemo, B. G.; Yaba, T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
In order to simulate a single rainfall event that occurred in the Labu catchment on April 7 and August 13, 2015, the HEC-HMS and soil moisture balance models were used. Based on the years that the peat swamp forest was converted into an oil palm plantation, the study plots within the watershed were divided into four plots: 2000, 2002, 2006, and 2010. In this study, two different hydrological models were employed such as the Soil moisture balance model and the Hydrologic Modeling System (HEC-HMS). A rainfall-runoff relationship for the sub-catchment was established using the Hydrologic Modeling System, HEC-HMS, coupled with recorded flow and rainfall data. This relationship was calibrated and then validated before being utilized for runoff estimation. The calibrated streamflow from the soil moisture balance model was compared with the HEC-HMS discharge values, which were used as the observed flow. The results show that the calibrated streamflow in the soil moisture balance model agrees with the observed streamflow data in the HEC-HMS. Following the two rainfall occurrences, the two models’ respective Nash-Sutcliffe Efficiency (Ef) values were 0.82 and 0.90 which implies that the observed flow and the predicted flow by the models are correlated and this shows a strong acceptable model performance for model simulation. This also means that the application of the HEC-HMS along with a recorded streamflow data shows the ability of the HEC-HMS model to calculate the streamflow volume in a double storm event at Labu basin.